2015
DOI: 10.1155/2015/513978
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicity and Antimicrobial Activity of an Ethanolic Extract from Leaves of Morus alba L. (Moraceae)

Abstract: This work evaluated an ethanolic extract from Morus alba leaves for toxicity to Artemia salina, oral toxicity to mice, and antimicrobial activity. Phytochemical analysis revealed the presence of coumarins, flavonoids, tannins, and triterpenes in the extract, which did not show toxicity to A. salina nauplii. No mortality and behavioral alterations were detected for mice treated with the extract (300 and 2000 mg/kg b.w.) for 14 days. However, animals that received the highest dose showed reduced MCV and MCHC as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 31 publications
2
38
0
3
Order By: Relevance
“…To further support the beneficial role of processing methods on African breadfruits, the present study revealed the effect of processing methods on the levels of anti-nutrient including; Phytate, Tannins, and Oxalate in African breadfruit seed as demonstrated in figure 2. Previous study has shown that consumption of these anti-nutritive factors at high levels often results in toxicity and eventual death (Olivierira et al, 2015), and in the present study, as shown in figure 2, the levels of anti-nutrient was significantly higher p<0.05 in the raw fraction of African breadfruit seeds IFNP, Vol. 16, No.…”
Section: Anti-nutrientsupporting
confidence: 67%
“…To further support the beneficial role of processing methods on African breadfruits, the present study revealed the effect of processing methods on the levels of anti-nutrient including; Phytate, Tannins, and Oxalate in African breadfruit seed as demonstrated in figure 2. Previous study has shown that consumption of these anti-nutritive factors at high levels often results in toxicity and eventual death (Olivierira et al, 2015), and in the present study, as shown in figure 2, the levels of anti-nutrient was significantly higher p<0.05 in the raw fraction of African breadfruit seeds IFNP, Vol. 16, No.…”
Section: Anti-nutrientsupporting
confidence: 67%
“…Fiori et al [38] found a positive correlation between tannin concentration and antifungal activity. Olivierira [12] reported on the antibiotic and antifungal properties of tannins. Similarly, Runsewe-Abiodun reported alleviation of skin rash in children fed on the African Breadfruit diet from the same locality [10].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of these anti-nutritive factors at high levels often results in toxicity and eventual death [12]. Studies have shown that the activity of these compounds may be reduced/removed by de-hulling, soaking, cooking, toasting and fermenting [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, this extract induced significant toxicity in mice. Specifically, oral administration of this extract (2,000 mg/kg) induced a reduction of immune cells, turgidity of contorted tubules in kidneys, infiltration of leukocytes around the liver centrilobular vein, and high dispersion of spleen white pulp [ 30 ]. Moreover, intraperitoneal administration of 300 and 2,000 mg/kg bw of mulberry leaf ethanol extracts for 14 days induced a greater degree of toxicity toward biochemical, hematological, and histological parameters in mice [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, oral administration of this extract (2,000 mg/kg) induced a reduction of immune cells, turgidity of contorted tubules in kidneys, infiltration of leukocytes around the liver centrilobular vein, and high dispersion of spleen white pulp [ 30 ]. Moreover, intraperitoneal administration of 300 and 2,000 mg/kg bw of mulberry leaf ethanol extracts for 14 days induced a greater degree of toxicity toward biochemical, hematological, and histological parameters in mice [ 30 ]. In the current study, aqueous extracts of mulberry leaves administered orally at doses of 1,000, 2,000 and 4,000 mg/kg bw did not induce any significant alterations in bw/weight gain, food consumption, ophthalmoscopy, clinical pathology, gross pathology, organ weights or histopathology over 28 days [ 31 ].…”
Section: Discussionmentioning
confidence: 99%